2013
DOI: 10.1186/1550-2783-10-22
|View full text |Cite
|
Sign up to set email alerts
|

Eight weeks of supplementation with a multi-ingredient weight loss product enhances body composition, reduces hip and waist girth, and increases energy levels in overweight men and women

Abstract: BackgroundNumerous natural products are marketed and sold claiming to decrease body weight and fat, but few undergo finished product-specific research demonstrating their safety and efficacy.ObjectiveTo determine the safety and efficacy of a multi-ingredient supplement containing primarily raspberry ketone, caffeine, capsaicin, garlic, ginger and Citrus aurantium (Prograde Metabolism™ [METABO]) as an adjunct to an eight-week weight loss program.MethodsUsing a randomized, placebo-controlled, double-blind design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 49 publications
(58 reference statements)
4
30
2
2
Order By: Relevance
“…Mentioned results showed that the supplement increased thermogenesis and accentuated body fat loss by 0.9 kg over 8 weeks. Furthermore, this is also in line with a recent study by Lopez et al [24] who demonstrated that a supplement containing caffeine and capsaicin for 8 weeks accentuated body weight and fat loss during a weight loss program. A significant decrease in BMI was also seen following the supplementation with 2 g/day of ginger powder among obese women for 12 weeks [10].…”
Section: Discussionsupporting
confidence: 79%
“…Mentioned results showed that the supplement increased thermogenesis and accentuated body fat loss by 0.9 kg over 8 weeks. Furthermore, this is also in line with a recent study by Lopez et al [24] who demonstrated that a supplement containing caffeine and capsaicin for 8 weeks accentuated body weight and fat loss during a weight loss program. A significant decrease in BMI was also seen following the supplementation with 2 g/day of ginger powder among obese women for 12 weeks [10].…”
Section: Discussionsupporting
confidence: 79%
“…But, since the natural abundance of RK is very low, it is prepared industrially by a variety of methods from chemical intermediates (Tateiwa et al, 1994). The present study demonstrated that RK suppressed adipogenesis and decreased lipid accumulation by inhibiting the expression of genes involved in adipogenesis and lipogenesis in 3T3-L1 adipocytes (Figures 1 and 2), which is consistent with the previous reports that RK has an anti-obese function in animal and human studies (Lopez et al, 2013;Meng et al, 2008;Morimoto et al, 2005). When given to male mice in high doses, RK has been shown to prevent the high-fat-dietinduced elevations in body weight and increase lipolysis in white adipocytes (Morimoto et al, 2005).…”
Section: Up-regulatory Effect Of Rk On the Expression Of Lipolytic Ansupporting
confidence: 81%
“…It was also shown that RK could reduce the weight of fat-diet-induced obese rat, suggesting that RK exerts anti-obesity functions by mediating lipid disorders, improving insulin resistance, and reversing leptin resistance (Meng et al, 2008). Moreover, a recent report showed that 8 weeks of supplementation with a multi-ingredient containing primarily RK reduced body weight and fat mass (Lopez et al, 2013). In addition, RK also exhibited preventive and therapeutic effects on nonalcoholic fatty hepatitis in rats fed high-fat diets (Wang et al, 2012).…”
Section: Up-regulatory Effect Of Rk On the Expression Of Lipolytic Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Other common ingredients include green tea extract, capsaicin and most recently raspberry ketones. Research is especially sparse with raspberry ketones with most data available coming from animal or cell culture models (Park, 2010;Morimoto et al, 2005), but recent work by Lopez (Lopez et al, 2013) and Kedia (Kedia et al, 2014) have shown positive impacts of differing multi-ingredient thermogenic supplement formulations in humans that included raspberry ketones along with other ingredients. Similar to caffeine, studies are available that have examined the sole impact of green tea extract or various catechins found in green tea on stimulating increased rates of fat oxidation and metabolic rate (Dulloo et al, 2000;Dulloo et al, 1999).…”
Section: Introductionmentioning
confidence: 97%